Comparison of hardenability and over-aging precipitation behaviour of three 7xxx aluminium alloys. Issue 6 (13th April 2019) - Zhou, Liang; Chen, Kanghua; Chen, Songyi; Zhang, Xinglin; Fan, Shumin; Huang, Lanping
ABSTRACT: The purpose of the paper is to compare hardenability and aging precipitation behaviour of three 7xxx aluminium alloys (7150, 7055 and 7056). The hardenability has been studied by Jominy test. The aging precipitation behaviour has been investigated according to their hardness and electrical conductivity after over-aging treatment. The micro-structural characterisation has been observed by scanning electron microscope and transmission electron microscope. These results show that AA7056 has the highest hardenability and sensitivity to over-aging treatment compared with AA7150 and AA7055. The highest w (Zn)/ w (Mg) ratio and the lowest Cu content of AA7056 are beneficial for inhibiting quench precipitates and decreasing the stability of meta-stable η ′ phase.